Best knock-knock book ever - Keller, Charles; Sinclair, Jeff (New York : Sterling Pub., 2000)
An alphabetically arranged collection of knock-knock jokes playing on names, initials, and phrases.
Includes index.
Keywords: Knock-knock jokes; Jokes